J Preg Neonatal Med 2017
DOI: 10.35841/pregnancy-neonatal.1000102
|View full text |Cite
|
Sign up to set email alerts
|

Feto-maternal outcomes of women with Rhesus iso-immunization in a Nigerian tertiary health care institution.

Abstract: Background: Fetomaternal haemorrhage may occur during pregnancy or at delivery and may lead to allo-immunization to the D antigen if the mother is Rhesus (Rh) negative and the baby is Rh-positive. Objectives: To determine the incidence, socio-demographic characteristics and pregnancy outcomes of Rh negative pregnant women in a Nigeria Tertiary health care institution. Methods: A review of the clinical records of all Rh-negative pregnant women, managed at the Nnamdi Azikiwe University Teaching Hospital (NAUTH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…In our study the incidence of Rh-negative pregnancy was 2.9 % which is similar to the national average of 3% to 5%. Which was comparable to the study done by [9][10][11][12][13] The prevalence in our study was higher than other studies because our center is tertiary referral center. In Table 2, our study was comparable according to parity, Agarwal et al who found 38.4% primigravida 33.6% second gravid 20% third gravid and 8% were multigravida.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study the incidence of Rh-negative pregnancy was 2.9 % which is similar to the national average of 3% to 5%. Which was comparable to the study done by [9][10][11][12][13] The prevalence in our study was higher than other studies because our center is tertiary referral center. In Table 2, our study was comparable according to parity, Agarwal et al who found 38.4% primigravida 33.6% second gravid 20% third gravid and 8% were multigravida.…”
Section: Discussionsupporting
confidence: 90%
“…15 Table 4 show comparison study with Shradha et al 15 Only 34% patients have received anti-D in previous pregnancies and according to Eleje et al 46.5% received anti D prophylaxis in the previous pregnancy. 10 Various studies have shown the risk of alloimmunization after postpartum anti D only is 2% risk after antepartum and postpartum anti D is 0.1% Similar results were shown by the studies Trina et al and Shradha et al where antenatal anti D prophylaxis was given to 30% cases and 34% cases respectively. 16,21 Our incidence was lower than Haripriya et al because of large sample size in their study.…”
Section: Discussionsupporting
confidence: 72%
“…The finding was corroborated by studies done in Nepal, 31 and Nigeria. 32 Conversely, this result was concordant with findings in Croatia, 25 and Iran. 26 Furthermore, this could be due to that male newborns have comparatively low levels of ligand which may not be able to process all the bilirubin formed from red blood cells and due to hormonal effects of transporter protein where testosterone down regulates membrane transporter protein which is involved in bilirubin metabolism.…”
Section: Discussionsupporting
confidence: 87%
“…Neonatal hyperbilirubinemia had a significant association with the feeding mode of neonates particularly with exclusive breastfeeding [AOR = 3.794; 95% CI (1.441-9.990)]. The association was described in studies conducted by Seyedi et al 38 and Eleje 32 This is due to decreased caloric intake/starvation, inhibition of hepatic excretion of bilirubin and an increase in intestinal absorption of bilirubin (enterohepatic circulation) 39 and a component of breast milk 40 are suggested mechanisms for the hyperbilirubinemia associated with breast-feeding.…”
Section: Discussionmentioning
confidence: 92%